1998
DOI: 10.1111/j.1399-3011.1998.tb00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the cross‐reactivity of rabbit antibodies raised against nonhomologous pairs of synthetic peptides derived from HIV‐1 gp120 proteins

Abstract: The immunological cross‐reactivity of several peptides with specific pattern‐property characteristics related to the epitopes of human immunodeficiency virus type 1 (HIV‐1) gp160/ 120 envelope proteins has been investigated. Proteins with similar primary structures can be expected to show functional or topographic similarities, such as specific epitopes which may cross‐react with antibodies derived from the immunisation of animals with other members of the same protein family. These structure‐function characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…As was shown in our previous studies of FGF peptidic antagonists [1,11] and HIV envelope agonists [12,13] such de novo designed peptides express the desired biological function.…”
Section: Resonant Recognition Model (Rrm)mentioning
confidence: 99%
“…As was shown in our previous studies of FGF peptidic antagonists [1,11] and HIV envelope agonists [12,13] such de novo designed peptides express the desired biological function.…”
Section: Resonant Recognition Model (Rrm)mentioning
confidence: 99%
“…A number of amino acid indices (402 have been published up to now [9]) have been found to correlate in some way with the biological activity of the whole protein. Previous investigations [1][2][3][4][5] have shown that the best correlation can be achieved with parameters, which are related to the energy of delocalised electrons of each amino acid. These findings can be explained by the fact that the electrons delocalised from the particular amino acid have the strongest impact on the electronic distribution of the whole protein.…”
Section: Methodsmentioning
confidence: 99%
“…Through an extensive study, the RRM has reached a fundamental conclusion: one RRM characteristic frequency characterizes one particular biological function or interaction [2,3]. Once the RRM characteristic frequency for a particular biological function or interaction has been determined, it is possible to identify then the individual amino acids so called "hot spots", or domains that contribute mostly to the characteristic frequency and thus to protein's biological function as well [3,4]. The RRM is based on the representation of the protein primary structure as a numerical series by assigning to each amino acid a physical parameter value relevant to the protein's biological activity.…”
Section: Methodsmentioning
confidence: 99%
“…The RRM analysis showed that these regions share the same characteristic frequency f1 (as gp160env proteins), but they also have their own more prominent characteristic at frequency f2=0.219+0.022 [1][2][3]12,13,15].…”
Section: Preliminary Researchmentioning
confidence: 99%
“…Only one common frequency component for all analysed isolates was obtained as prominent peak at frequency f1=0.185+0.001 (signal-to-noise=484) in the crosspectral function (Fig.1). According to RRM concepts, it can be proposed that this frequency characterises the common biological behavior of all analysed proteins [1][2][3][4]12,13,15]. Figure 1 Cross-spectral function of gp160 env proteins from 19 different isolates revealing the characteristic frequency at f1=0.1855.…”
Section: Preliminary Researchmentioning
confidence: 99%